Globalization, socio-economic status and welfare chauvinism: European perspectives on attitudes toward the exclusion of immigrants. (June 2013) - Mewes, Jan; Mau, Steffen
This article addresses the question of whether globalization impacts individual preferences to exclude immigrants from national welfare systems ('welfare chauvinism'). Intergroup contact theory and arguments from the 'new cosmopolitanism' debate suggest that cross-border social contacts ('social globalization') foster a willingness to include and accept newcomers. However, group conflict theory suggests that trade openness ('economic globalization') can unleash feelings of insecurity and trigger welfare chauvinism. While these approaches point in different directions, we argue that the impact of globalization on welfare chauvinism differs across socio-economic status groups. Using cross-national data from the European Social Survey 2008/2009, we find scarce support for the hypothesis that social globalization reduces welfare chauvinism in general. However, there is evidence that it diminishes exclusionary attitudes among those with relatively high socio-economic statuses. Moreover, we find no general evidence for an impact of economic globalization on chauvinism, but a positive interaction of intensified engagement with global market forces and higher socio-economic status.